Application of indicator simulation to modelling the lithological properties of a complex confining layer - Bierkens, Marc F.P.; Weerts, Henk J.T. (Elsevier BV, 1994)
This paper describes a three-dimensional simulation of the texture distribution of a complex confining layer. Indicators are used to characterize statistically the spatial variability of the different texture classes. "Sequential indicator simulation" is then used to generate equiprobable realisations of texture classes, conditional on the textures found at the drilling sites. By successively assigning values for conductivities and porosities to the simulated texture classes, fields of conductivities and porosities can be obtained. These can in turn be used as input for a groundwater model in a Monte Carlo analysis. A case study is presented to demonstrate the application of sequential indicator simulation to the stochastic modelling of the texture distribution of a complex confining layer in the Netherlands. The results are validated using the data from a lithological cross-section with a very small borehole spacing.
Keywords: Soil Science